2010
DOI: 10.1152/ajpregu.00534.2009
|View full text |Cite
|
Sign up to set email alerts
|

Bmp2 and Bmp4 exert opposing effects in hypoxic pulmonary hypertension

Abstract: The bone morphogenetic protein (BMP) type 2 receptor ligand, Bmp2, is upregulated in the peripheral pulmonary vasculature during hypoxia-induced pulmonary hypertension (PH). This contrasts with the expression of Bmp4, which is expressed in respiratory epithelia throughout the lung. Unlike heterozygous null Bmp4 mice (Bmp4(LacZ/+)), which are protected from the development of hypoxic PH, mice that are heterozygous null for Bmp2 (Bmp2(+/-)) develop more severe hypoxic PH than their wild-type littermates. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 32 publications
6
68
0
Order By: Relevance
“…This is consistent with published data indicating that both Id1 and Id3 are transcriptional targets of BMP-activated SMADs in a variety of cells types (27). Furthermore, since our laboratory has previously shown that hypoxia-induced PH is dependent on intact BMP signaling (2,8,9), and since ID1-and ID3-positive VSMCs are also closely associated with BMP-2-and BMP-4-expressing cells in small peripheral vessels and alveoli of the hypoxic lung (2,8), these findings are consistent with the hypothesis that hypoxia induces VSMC expression of ID1 and ID3 in the intact pulmonary vasculature in a BMP-dependent fashion. However, while Id2 is also a bona fide BMP target gene in a variety of different cell types (15,20,37), its expression is unaffected by hypoxia or BMP treatment in these cultured mouse PASMCs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with published data indicating that both Id1 and Id3 are transcriptional targets of BMP-activated SMADs in a variety of cells types (27). Furthermore, since our laboratory has previously shown that hypoxia-induced PH is dependent on intact BMP signaling (2,8,9), and since ID1-and ID3-positive VSMCs are also closely associated with BMP-2-and BMP-4-expressing cells in small peripheral vessels and alveoli of the hypoxic lung (2,8), these findings are consistent with the hypothesis that hypoxia induces VSMC expression of ID1 and ID3 in the intact pulmonary vasculature in a BMP-dependent fashion. However, while Id2 is also a bona fide BMP target gene in a variety of different cell types (15,20,37), its expression is unaffected by hypoxia or BMP treatment in these cultured mouse PASMCs.…”
Section: Discussionsupporting
confidence: 93%
“…As reported previously (2,8,9,22), this revealed activation of the BMP pathway by hypoxia, as indicated by increased COOHterminal phosphorylation of the receptor-activated SMADs 1, 5, and 8 (pS1/5/8) (Supplemental Fig. S8, A and B).…”
Section: Regulation Of Pulmonary Id1-3 Expression Levels By Hypoxiasupporting
confidence: 84%
See 2 more Smart Citations
“…Several studies revealed that there was interaction between BMP2 and BMP4. 16,17 We found that BMP4 treatment did not affect BMP2 protein expression in cardiomyocytes ( Figure S11C). …”
Section: Bmp4 Induces Cardiomyocyte Hypertrophy and Apoptosis Throughmentioning
confidence: 93%